Energy estimates of bounded solutions of the Dirichlet problem for a class of nonlinear fourth-order elliptic equations - Voitovich, M.V. (Труды Института прикладной математики и механики, 2012)
We consider a class of nonlinear elliptic fourth-order equations with the principal part satisfying a strengthened coercivity condition, absorption and a lower-order term. It is supposed that the lowerorder term of the equations admits the growth rates of derivatives of unknown function coinciding with the exponents of the corresponding energy space. At the same time, we do not suppose that the lowerorder term satisfies a sign condition. Energy estimates of bounded generalized solutions of the Dirichlet problem for equations of the given class are established. Рассматривается класс нелинейных эллиптических уравнений четвертого порядка со старшими коэффициентами, удовлетворяющими условию усиленной коэрцитивности, абсорбцией и младшим коэффициентом, имеющим рост порядков, совпадающих с показателями соответствующего уравнениям энергетического пространства, относительно производных неизвестной функции. Не делается никаких предположений о выполнении определенных знаковых условий относительно младшего коэффициента. Устанавливаются энергетические оценки ограниченных обобщенных решений задачи Дирихле для уравнений рассматриваемого класса. Розглядається клас нелiнiйних елiптичних рiвнянь зi старшими коефiцiєнтами, якi задовольняють умову пiдсиленої коерцитивностi, абсорбцiєю i молодшим коефiцiєнтом, що має зростання порядкiв, якi спiвпадають з показниками вiдповiдного рiвнянням енергетичного простору, вiдносно похiдних невiдомої функцiї. Не робиться жодних припущень щодо виконання певних знакових умов вiдносно молодшого коефiцiєнта. Встановлено енергетичнi оцiнки обмежених узагальнених розв’язкiв задачi Дiрiхле для рiвнянь, що розглядаються.